2021
DOI: 10.1038/s41598-021-85962-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity of docetaxel, carboplatin, and doxorubicin in patient-derived triple-negative breast cancer xenografts

Abstract: Triple-negative breast cancer (TNBC) is highly responsive to neoadjuvant polychemotherapy regimens including anthracyclines, taxanes, and, more recently, carboplatin. However, there is inadequate information on the individual contribution of each of these agents to the global activity of the combinations, and the use of combinations of up to four of these drugs is associated with relevant toxicity. Identifying single-drug activity in the clinical neoadjuvant setting is challenging. We developed patient-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Reduced sensitivity of cancer cells to doxorubicin can be shown by dysregulation of apoptotic marker expressions. 8 , 42 , 43 Our RT-PCR analysis suggested that doxorubicin might have a weaker pro-apoptotic activity in TMEPAI positive cells than knock-out cells. However, we acknowledge that a better correlation to apoptotic markers will be achieved if we analyze using Western blotting.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Reduced sensitivity of cancer cells to doxorubicin can be shown by dysregulation of apoptotic marker expressions. 8 , 42 , 43 Our RT-PCR analysis suggested that doxorubicin might have a weaker pro-apoptotic activity in TMEPAI positive cells than knock-out cells. However, we acknowledge that a better correlation to apoptotic markers will be achieved if we analyze using Western blotting.…”
Section: Discussionmentioning
confidence: 84%
“… 2 , 5–7 Despite the benefit of systemic chemotherapy in improving outcomes of TNBC patients, the problem with chemoresistance is significant, which accounts for about 90% of treatment failure cases. 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…The concentrations at which cell growth is inhibited by 50% (GI50) after 72 hrs exposure of cells to furyl carboxamide derivatives 3, 5, 7, and Doxorubicin were obtained from dose-response curves after considering the initial optical density acquired at the time of treatment. GI50 values are presented in Table 1, while Figure 1 shows the structure of Doxorubicin as a reference drug used as an antiproliferation-active compound (12). As can be deduced from the table, the three compounds 3, 5, and 7 show significant and almost identical cellular growth inhibitory activity against human carcinoma colon HCT-116 cell line in the examined concentration range (0.01-100 μM).…”
Section: Growth Inhibitory and Cytotoxic Effect Of The Synthesized Fu...mentioning
confidence: 98%
“…Commercially available cancer drugs exhibit a variety of systemic toxic effects, due to many factors including high toxicity, low bioavailability, high drug dispersion in the body, and absence of drug delivery and controlled release devices [ 8 ]. The standard chemotherapy against TNBC is based on an anthracycline-taxane combination, but a significant proportion (30–40%) of patients with early-stage TNBC develop metastatic disease and succumb to cancer, so some modifications in the traditional TNBC chemotherapy regimens are necessary [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%